PEMANFAATAN DIGITAL MARKETING DALAM MANAJEMEN PEMASARAN PADA UMKM DESA LANCANG KUNING - Evita Sandra,; Ulfa Oktavani Nasution,; Armansyah, Armansyah (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
In the digital age, businesses must adopt digital marketing trends to increase targets and sales. Digital marketing, which is becoming a tremendous business phenomenon on the internet, allows companies to introduce and promote products more effectively. In Lancang Kuning Village, the community service mechanism for digital marketing involves planning, training, and evaluation. MSME participants, divided by business field, collaborate in planning training programs. During the activity, they understand how to promote products through digital media. The final evaluation provides feedback to MSME players about products and marketing strategies, including direct interaction with users through social media. It not only provides insight into the acceptance of the product, but also allows an assessment of the benefits and disadvantages of the product or marketing strategy that has been adopted.